Socio-demographic profile of TB-HIV co-infected adults and it’s association with tuberculosis treatment outcome, in a South Indian city - M. V., Arun Mohan; H. J., Tejaswi; T. S., Ranganath (International Journal Of Community Medicine And Public Health, 2016)
Background: Human immune deficiency virus (HIV) and tuberculosis (TB) are major public health challenges and are intricately linked to other public health challenges like malnutrition, unemployment, alcoholism, drug abuse, poverty, homelessness and even mortality. In 2013, 360,000 deaths from HIV associated TB equivalent to 25% of all TB deaths, and around 25% of the estimated 1.5 million deaths from HIV/AIDS .Prognosis in these diseases depends on factors such as health seeking behavior and compliance to drug regimen which further depend upon various socio-demographic factors, hence it is decided to study the socio-demographic correlates of TB-HIV co-infected adults and their association with TB treatment outcome in Bangalore Municipality area. Methods: A longitudinal observational study was carried out, from November 1st 2010 to December 30th 2011, on HIV-TB co-infected adults receiving Revised National TB control program’s (RNTCP) Directly Observed Treatment Short-course (DOTS) from 5 randomly selected Tuberculosis units of Bangalore Municipality area, by interview method using a questionnaire. Results: Majority of the 162 HIV-TB co-infected adults studied were males (74%), belonging to fourth decade of life, and most came from low socio-economic stratum and most were educated only till middle school (70%). Most common occupation was unskilled labour (17.3%), and among women, 58% were house wives. Disability due to the diseases had led to unemployment of many who were earlier employed. Most patients belonged to Hindu (80.2%) religion, live in nuclear families (67.9%), and come from urban slums (55.8%). Three fourths of the patients were either currently married (103, 63.6%) or had been married. TB treatment success rate was 90.5%. Although there were differences in the proportion of successful and unsuccessful outcomes of TB treatment among groups pertaining to socio-demographic attributes of patients, none of these differences were statistically significant. Conclusions: HIV-TB co-infection was common among males, middle aged adults, low socio-economic class, those with low education and among unskilled labourers, but none of these socio-demographic attributes had significant relation with the TB treatment outcome.